‘Twisted’ electrons - Larocque, Hugo; Kaminer, Ido; Grillo, Vincenzo; Leuchs, Gerd; Padgett, Miles J.; Boyd, Robert W.; Segev, Mordechai; Karimi, Ebrahim (Contemporary Physics, 2018)
Electrons have played a significant role in the development of many fields of physics during the last century. The interest surrounding them mostly involved their wave-like features prescribed by the quantum theory. In particular, these features correctly predict the behaviour of electrons in various physical systems including atoms, molecules, solid-state materials, and even in free space. Ten years ago, new breakthroughs were made, arising from the new ability to bestow orbital angular momentum (OAM) to the wave function of electrons. This quantity, in conjunction with the electron’s charge, results in an additional magnetic property. Owing to these features, OAM-carrying, or twisted, electrons can effectively interact with magnetic fields in unprecedented ways and have motivated materials scientists to find new methods for generating twisted electrons and measuring their OAM content. Here, we provide an overview of such techniques along with an introduction to the exciting dynamics of twisted electrons.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Electrons; matter waves and particle beams; nanophysics; orbital angular momentum; quantum physics